α- and α'-lithiation-electrophile trapping of N-thiopivaloyl and N-tert-butoxythiocarbonyl α-substituted azetidines: rationalization of the regiodivergence using NMR and computation - Jackson, KE; Mortimer, CL; Odell, B; McKenna, JM; Claridge, TDW; Paton, RS; Hodgson, DM (American Chemical Society, 2015)
(1)H NMR and computational analyses provide insight into the regiodivergent (α- and α'-) lithiation-electrophile trapping of N-thiopivaloyl- and N-(tert-butoxythiocarbonyl)-α-alkylazetidines. The magnitudes of the rotation barriers in these azetidines indicate that rotamer interconversions do not occur at the temperature and on the time scale of the lithiations. The NMR and computational studies support the origin of regioselectivity as being thiocarbonyl-directed lithiation from the lowest energy amide-like rotameric forms (cis for N-thiopivaloyl and trans for N-tert-butoxythiocarbonyl).